L‐histidine improves water retention of heat‐induced gel of chicken breast myofibrillar proteins in low ionic strength solution. (2nd March 2016) - Chen, Xing; Li, Yong; Zhou, Ruiyun; Liu, Zhaiming; Lu, Fengzhi; Lin, Huang; Xu, Xinglian; Zhou, Guanghong
Summary: The effects of 5 mm l ‐histidine (l ‐His) on water‐binding capacity, gel strength, thermal gelling properties of chicken breast myofibrillar proteins (MPs) in 1 mm NaCl or 0.6 m NaCl solutions (pH 7.0) were investigated.l ‐His could significantly increase the solubility and thermal gelling ability of MPs in 1 mm NaCl.l ‐His at 1 mm NaCl shortened the water relaxation time and decreased the water mobility of MPs gel.l ‐His promoted the formation of MPs gel structure with small pores and thin strands at 1 mm NaCl. These resulted in the enhanced water retention and weak gel strength of MPs in low ionic strength solution. The water‐binding capacity of MPs gels formed in 1 mm NaCl containing 5 mm l ‐His was equivalent to that with 0.6 m NaCl. The information could offer certain theoretical foundation to applyl ‐His as sodium salt substitute for developing low‐salt meat gelling product with high yield. Abstract : Effects of 5 mm l ‐histidine on the gel properties of chicken breast myofibrillar proteins in low ionic strength solution.